Detecting sources of water leakage in fractured limestone: Case study in Mokattam District, Egypt - Mamdouh Mohamed AlSittawy; Eman R. Nofal; Amany T. Eid (Water Science)
The paper investigates the sources of water leakage in Mokattam, Cairo, Egypt. It is considered a high-risk zone for landslides due to the presence of problematic soil, topography, and water conditions. The objective is to mitigate the negative impact of underground water on landslide disasters. The proposed methodology involves field visits, satellite image processing, Ground Penetration Radar scanning, chemical and isotope analysis of water, and evaluating the water and sanitary networks within the study area. The findings revealed that the underground water is formed because of the continuous leakage from the existing networks. Moreover, there was no evidence of any aquifers, particularly at Ain Mosa floating point. Thus, the accumulated water in the unsaturated zone is not sustainable for long-term development for its limited potential and poor quality. Consequently, immediate action plan is required to assess and upgrade the water and sanitary networks through the implementation of innovative technologies for such hydrogeologic conditions